2001
DOI: 10.1002/mrm.10043
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular acidification and volume increases explain R2 decreases in exercising muscle

Abstract: Exercise-induced decreases in the 1 H transverse relaxation rate (R 2 ) of muscle have been well documented, but the mechanism remains unclear. In this study, the hypothesis was tested that R 2 decreases could be explained by pH decreases and apparent intracellular volume (V i ) increases. 31 P and 1 H spectroscopy, biexponential R 2 analysis, and imaging were performed prior to and following fatiguing exercise in iodoacetate-treated (IAA, to inhibit glycolysis), NaCN-treated (to inhibit oxidative phosphorylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
82
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(91 citation statements)
references
References 37 publications
8
82
1
Order By: Relevance
“…It has also been used to detect changes in muscle function consequent to clinical conditions such as peripheral vascular disease (31). The interpretation of these data, however, is limited by the absence of a full theoretical understanding of which physiological variables produce the mfMRI response and how their contributions may differ during and after exercise.Multiexponential relaxation analysis has shown that the major contribution to signal intensity (SI) changes in mfMRI is made by the increase in the transverse relaxation time constant (T2) of intracellular water protons (4,22,23). Proposed explanations for intracellular T2 increases include the accumulation of end products of cellular energy metabolism, which cause water to move into the cell (4, 21), decreased intracellular pH (4, 8), and water shifts from an intracellular compartment possessing a short T2 (ϳ20 ms) to a second intracellular compartment having a longer T2 (ϳ40 ms) (22, 23).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…It has also been used to detect changes in muscle function consequent to clinical conditions such as peripheral vascular disease (31). The interpretation of these data, however, is limited by the absence of a full theoretical understanding of which physiological variables produce the mfMRI response and how their contributions may differ during and after exercise.Multiexponential relaxation analysis has shown that the major contribution to signal intensity (SI) changes in mfMRI is made by the increase in the transverse relaxation time constant (T2) of intracellular water protons (4,22,23). Proposed explanations for intracellular T2 increases include the accumulation of end products of cellular energy metabolism, which cause water to move into the cell (4, 21), decreased intracellular pH (4, 8), and water shifts from an intracellular compartment possessing a short T2 (ϳ20 ms) to a second intracellular compartment having a longer T2 (ϳ40 ms) (22, 23).…”
mentioning
confidence: 99%
“…Multiexponential relaxation analysis has shown that the major contribution to signal intensity (SI) changes in mfMRI is made by the increase in the transverse relaxation time constant (T2) of intracellular water protons (4,22,23). Proposed explanations for intracellular T2 increases include the accumulation of end products of cellular energy metabolism, which cause water to move into the cell (4,21), decreased intracellular pH (4,8), and water shifts from an intracellular compartment possessing a short T2 (ϳ20 ms) to a second intracellular compartment having a longer T2 (ϳ40 ms) (22,23).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Non-invasive NMR studies revealed different values of acidification; however, all results are within a pH range of 6.0-7.0 (Meynial- Denis et al 1993;Mizuno et al 1994;Damon et al 2002). Iwanaga et al (1991) described an even more significant pH decrease after the contraction of muscle using 31 P-MRS spectra measurement.…”
Section: Discussionmentioning
confidence: 99%